(untitled) (Research, Society and Development, 2021)
An integrative review aimed to analyze scientific productions about national public policies regarding disabled people and their family. Data collection was performed in October 2020, in all available databases at Virtual Health Library (BVS), using “public policy”, “disability”, and “family” as descriptors. From the eligibility requirements, 16 documents were selected. When reading the articles, public policies focused on people with disabilities are still reduced. We also note the absence of policies aimed at training, information and care for caregivers. The results showed that scientific productions about public policies that support a person with disabilities and his family are unsatisfactory in the middle of scientific productions.